(untitled) (Journal of Parents and Teachers, 2017)
Scouting is a school of commitment that seeks to create people who can build a better world. From its educational approach seeks, even from the very initial stages, to educate constructors of a better society using an action-reflection-action methodology that not only produces a fairer, more free and plural, peaceful society... but that provides essential thoughts about it.